PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PERUSAHAAN MAJU MAKMUR BANJARMASIN - Fariansyah -; Defin Shahrial Putra (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This study aims to examine: (1) leadership style influences on employee performance Maju Makmur Company Banjarmasin, (2) commitment influences on employee performance MajuMakmur Company Banjarmasin and (3) leadership style and organizational commitment influence on employee performance Maju Makmur Company Banjarmasin. The study population is all employees in Maju Makmur Company Banjarmasin and the sample size is 84 respondents which data is analyzed using the Double Linear Regression.The results show 1) leadership style significantly influences on employee performance Maju Makmur Company Banjarmasin, 2) commitment significantly influences on employee performance Maju Makmur Company Banjarmasin and 3) leadership style and organizational commitment significantly influence on employee performance Maju Makmur Company Banjarmasin, this indicates that the leaders understand what can motivate their employees. In addition, commitment is the nature of employees’ loyalty to organization and is an ongoing process that expresses their attention to the organization and subsequent success.